Does masticatory muscle hyperactivity occur in individuals presenting temporomandibular disorders? - Delaine Rodrigues-Bigaton; Rosemary Berto; Anamaria Siriani Oliveira; Fausto Bérzin (Universidade Estadual de Campinas, 2016)
Aim: To verify whether patients with temporomandibular disorders (TMD) present masticatory muscle hyperactivity with the mandible in the rest position. Method: Forty-six women were selected (18-33 years-old, mean age = 22.7 ± 3.52 years), 31 with TMD (experimental group) and 15 without TMD (control group). Electromyography (EMG) was performed in two situations: 1) with the mandible in the rest position and 2) in maximal dental clenching. RMS (root mean square) was used for EMG signal analysis. Data were analyzed statistically by the Mann Whitney U-test. Result: The experimental groups presented increased EMG activity of the muscles evaluated with the mandible in the rest position compared to the control. In maximal dental clenching, no differences were observed between the groups. Analyzing the percentage of EMG activity at rest, the control group presented EMG activity around 1 to 6% of maximal dental clenching and the experimental group, around 1 to 12% of the same activity. Conclusion: The experimental group presented an increase in EMG activity at rest in the studied muscles, mainly in the anterior portion of the temporal muscle, bilaterally. However, this increase should not be called muscular hyperactivity, but should rather be considered as an important sign of TMD.